Genetic variability of tomato leaf curl new delhi virus infecting cucumber in sub-Himalayan plains in Eastern India - Karmakar, A.; Sarkar, T.; Chakraborty, P.; Biswas, K. K.; Saha, A.; Saha, D. (International Journal of Agricultural Technology, 2021)
Cucumber (Cucumis sativus, Cucurbitaceae) is a vegetable crop widely cultivated in India.Disease survey was conducted from December, 2016 to March, 2017in different locations of sub-Himalayan plains in Eastern India. During survey, leaf curl disease of cucumber was found to be one of the most serious threats in cucumber production. Based on disease symptoms, thirty infected and five healthy leaf samples were collected. Twenty out of thirty infected samples were found positive for begomovirus infection upon PCR with begomovirus specific universal primers. Amplified products were cloned, sequenced and four representative sequences (one from each location) were submitted to GenBank. BLAST analysis of the isolates showed 97-99% nucleotide identity with Tomato leaf curl New Delhi virus (ToLCNDV) infecting cucumber from Bangladesh. A phylogenetic tree was constructed and a two-dimensional colour-coded sequence identity matrix was generated to find out the relationship between present ToLCNDV isolates and other isolates of India and neighboring countries. From the present study it was evident that the present isolates were closely related to Bangladeshi isolates rather than other Indian isolates.This might becorrelated to different factors like-availability of vectors, weather condition and agricultural practices in this area are similar with the neighbor country Bangladesh